2016
DOI: 10.1080/17425247.2017.1242574
|View full text |Cite
|
Sign up to set email alerts
|

Peptides as a therapeutic avenue for nanocarrier-aided targeting of glioma

Abstract: Very few successful interventions have been possible in glioma therapy owing to its aggressive nature as well as its hindrance of targeted therapy together with the limited access afforded by the blood-brain barrier (BBB). With the advent of nanotechnology based delivery vehicles such as micelles, dendrimers, polymer-based nanoparticles and nanogels, the breach of the BBB has been facilitated. However, there remains the issue of targeted therapy for glioma cells. Peptide-mediated surface modification of nanoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…The promising advantages of low immunogenicity, intrinsic cell targeting properties, and enhanced stability in circulation make EVs an ever more attractive concept in targeted drug therapy, and highlight their potential in the therapy of various diseases, including glioma [ 12 ]. Recently, cell penetrating peptides have emerged as a critical player in targeted therapy for glioma by embellishing nanocarriers to deliver anti-tumor drugs [ 18 ]. During the current investigation, we aimed to explore the therapeutic effect of ICG/PTX transferred by RGE-EV in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…The promising advantages of low immunogenicity, intrinsic cell targeting properties, and enhanced stability in circulation make EVs an ever more attractive concept in targeted drug therapy, and highlight their potential in the therapy of various diseases, including glioma [ 12 ]. Recently, cell penetrating peptides have emerged as a critical player in targeted therapy for glioma by embellishing nanocarriers to deliver anti-tumor drugs [ 18 ]. During the current investigation, we aimed to explore the therapeutic effect of ICG/PTX transferred by RGE-EV in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Coating cell permeable peptides on the surface of nanoparticles could serve this purpose. A detailed review about peptides for targeting glioma cells can be found 17 . This review mainly focuses on crossing the BBTB.…”
Section: General Background On the Blood-brain Barriermentioning
confidence: 99%
“…Coating cell-permeable peptides might accomplish this on the surface of nanoparticles. A comprehensive review of peptides for glioma cell targeting may be obtained [ 33 ]. This review is mostly concerned with crossing the BBTB.…”
Section: General Background On the Blood–brain Barriermentioning
confidence: 99%